INSECTICIDAL PROPERTY OF BIOINSECTICIDE AGAINST BOVICOLA OVIS - A.A, Dzhalolov; F.S., Pulotov; A.Sh. , Ismailov (PT. Antis International Publisher, 2024)
The article presents information about the biology of the causative agent of sheep bovicolosis, fleas Bovicola ovis, clinical symptoms of the disease, the effectiveness of the use of a new local drug